Sleep/wake behaviour of endurance cyclists before and during competition - Lastella, M.; Roach, G. D.; Halson, S. L.; Martin, D. T.; West, N. P.; Sargent, C. (Journal of Sports Sciences, 2015)
Good sleep is critical for optimising recovery and athletic performance. Yet, few studies have investigated how athletes sleep before and during competition. The aim of this study was to determine whether such sleep is poorer than that before a usual training day. Twenty-one male endurance cyclists` (age: 19.9 ± 1.7 years) sleep/wake behaviour was assessed using wrist activity monitors for 11 nights, including a six-night baseline training phase, three nights before competition and two nights during competition. Cyclists had less sleep on the night before competition (6.5 ± 0.9 h) and during the first night of competition (6.8 ± 0.8 h) than at baseline (7.4 ± 0.6 h). Cyclists also went to bed and woke up earlier during competition than at baseline. Competition schedules and competition itself can disrupt the sleep/wake behaviour of athletes during competition. Future investigations should examine sleep during three stages of competition (i.e. before, during and after competition). This will help coaches develop a greater understanding of how sleep changes during different phases of competition and enable them to plan post-competition training programmes to ensure appropriate rest and recovery is obtained.